16 weeks of moderate intensity resistance exercise improves strength but is insufficient to alter brain structure in Gulf War Veterans with chronic musculoskeletal pain: a randomized controlled trial - Van Riper, Stephanie M.; Ninneman, Jacob V.; Stegner, Aaron J.; Riedner, Brady A.; Ellingson, Laura D.; Dougherty, Ryan J.; O’Connor, Patrick J.; Roberge, Gunnar A.; Alexander, Andrew L.; Dean, Doug C.; Barnes, Jill N.; Cook, Dane B. (Frontiers in Neuroscience, 2025)
IntroductionChronic widespread musculoskeletal pain (CMP) is a primary condition of Veterans who were deployed to the Persian Gulf War. The mechanisms that underlie CMP in these Veterans are unknown and few efficacious treatment options exist. This study tested the effects of 16 weeks of resistance exercise training (RET) on gray matter (GM) volume and white matter (WM) microstructure in Gulf War Veterans (GWVs) with CMP compared to GWV waitlist controls (WLC).MethodsFifty-four GWVs were randomly assigned to 16 weeks of RET (n = 28) or WLC (n = 26). Training involved 10 resistance exercises to involve the whole body, was supervised and individually tailored, and progressed slowly to avoid symptom exacerbation. Outcomes assessed at baseline, 6, 11 and 17 weeks and 6- and 12-months post-intervention included GM volume (voxel-based morphometry), WM microstructure (diffusion tensor imaging), pain [short form McGill Pain Questionnaire (SF-MPQ) and 0–100 visual analog scale (VAS)], fatigue (0–100 VAS), and mood (Profile of Mood States). Muscular strength was assessed at baseline, 8 and 16 weeks, and training volume was tracked throughout the 16-week intervention. Primary analyses used linear mixed effects models with Group, Time, and the Group*Time interaction as fixed factors and subject and slope as random factors to test the differential effects of RET and WLC on brain structure and symptoms. All neuroimaging analyses used the False Discovery Rate to correct for multiple comparisons at an alpha of 0.05.ResultsStrength increased significantly across the trial for the RET group (p < 0.001). There were significant Group*Time interaction effects for pain ratings (SF-MPQ total; p < 0.01) and the Profile of Mood States total mood disturbance score (p < 0.01). There were no Group or Group*Time effects for GM volume or WM microstructure. There were no significant associations between strength, symptoms, and brain structure (p > 0.05).ConclusionSixteen weeks of low-to-moderate intensity RET (i) improved musculoskeletal strength and (ii) did not exacerbate symptoms, but (iii) was insufficient to alter brain structure in GWVs with CMP.